2021
DOI: 10.1016/j.radonc.2021.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Planning target volume margin assessment for online adaptive MR-guided dose-escalation in rectal cancer on a 1.5 T MR-Linac

Abstract: This study assessed the margins needed to cover tumor intrafraction motion during an MRguided radiotherapy (MRgRT) dose-escalation strategy in intermediate risk rectal cancer. Methods: Fifteen patients with rectal cancer were treated with neoadjuvant short-course radiotherapy, 5x5 Gy, according to an online adaptive workflow on a 1.5 T MR-linac. Per patient, 26 3D T2 weighted MRIs were made; one reference scan preceding treatment and five scans per treatment fraction. The primary tumor was delineated on each s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 35 publications
0
8
1
Order By: Relevance
“…Differently from previous studies, which supposed a possible impact of tumor location and stage on tumor motion itself, we found no correlation between these factors and MM, relying on the better morphological detail provided by MR images [26][27][28]. Considering these and other differences in the methodology applied in the previous studies, our results are not directly comparable with others.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Differently from previous studies, which supposed a possible impact of tumor location and stage on tumor motion itself, we found no correlation between these factors and MM, relying on the better morphological detail provided by MR images [26][27][28]. Considering these and other differences in the methodology applied in the previous studies, our results are not directly comparable with others.…”
Section: Discussioncontrasting
confidence: 99%
“…MRgRT is currently considered as one of the best strategies to carry out dose escalation protocols in LARC, in particular with the application of online adaptive (OA) MRgRT protocols, in order to increase the dose-dependent therapeutic efficacy [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…With the advent of MRI-Linac hybrid devices it has become possible to considerably reduce planning target volume margins as treatment plans can be adapted to the anatomy of the day based on daily MRI scans. Several studies have shown that planning target volumes required to cover the remaining intrafractional motion with or without rectal filling can be reduced to 4 mm using an online adaptive workflow [2] , [6] , [9] . The present study demonstrates that the addition of rectal ultrasound gel results in more accurate target volume definition in rectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to being able to use the superior soft tissue contrast of the MRI during treatment, the MRI-Linac also allows the treatment plan to be adapted daily to the anatomy of the day. These advantages allow the safety margins for rectal cancer dose escalation to be reduced to a few millimeters instead of 1 cm or more (Bonomo, Lo Russo et al 2021, Eijkelenkamp, Boekhoff et al 2021. At the same time, with such small margins accurate target volume definition becomes more crucial.…”
Section: Introductionmentioning
confidence: 99%
“…Intrafractional motion during the online ART process remains a major concern because the adaptive plan may no longer be relevant to the anatomy if substantial anatomic changes such as bulk or peristaltic motions occur during the planning process. For example, it was reported that a 6-mm planning margin was required to compensate for the intrafraction GTV motion occurring during the online ART process for rectal tumors treated on a 1.5 T MRI-linac (Eijkelenkamp et al , 2021). The margin can be reduced to 4 mm, if the procedure time can be controlled within 15 min.…”
Section: Online Adaptive Mrigrtmentioning
confidence: 99%